Acute Respiratory Distress Syndrome Caused by Influenza B Virus Infection in a Patient with Diffuse Large B-Cell Lymphoma - Silvio A. Ñamendys-Silva; María O. González-Herrera; Julia Texcocano-Becerra; Angel Herrera-Gómez (Case Reports in Medicine)
Influenza B virus infections are less common than infections caused by influenza A virus in critically ill patients, but similar mortality rates have been observed for both influenza types. Pneumonia caused by influenza B virus is uncommon and has been reported in pediatric patients and previously healthy adults. Critically ill patients with pneumonia caused by influenza virus may develop acute respiratory distress syndrome. We describe the clinical course of a critically ill patient with diffuse large B-cell lymphoma nongerminal center B-cell phenotype who developed acute respiratory distress syndrome caused by influenza B virus infection. This paper emphasizes the need to suspect influenza B virus infection in critically ill immunocompromised patients with progressive deterioration of cardiopulmonary function despite treatment with antibiotics. Early initiation of neuraminidase inhibitor and the implementation of guidelines for management of severe sepsis and septic shock should be considered.